Looking Back: Reviewing the Challenges of Policy Development During the COVID-19 Pandemic for a TNE Partnership in Higher Education - Bremner, Duncan James; Ansari, Imran Shafique; MacDougall, Jennifer; Hussain, Sajjad; Ma, Mingda; Ponciano, Joao; Liu, Xingang; Gamage, Kelum A. A.; Abbas, Hasan; Imran, Muhammad Ali (Frontiers in Education, 2021)
This paper takes a longitudinal view over the year 2020, documenting how Higher Education policy development at an institutional level was undertaken for a Transnational Education (TNE) program between a Sino-UK partnership comprising the University of Glasgow (UofG) and the University of Electronics, Science and Technology in Chengdu (UESTC), China in response to the Covid-19 pandemic. It explores the approach to policy development under normal circumstances, contrasting this with the techniques used during the emergence of the epidemic and explains how the unfolding situation impacted on policy. It demonstrates how the application of scenario planning and crisis management techniques can be used effectively to develop a clear and prescriptive policy for staff operating in partnership. It also demonstrates how the use of industry standard tools combined with careful analysis and planning can minimize disruption to student learning, teaching and assessment. The paper then goes on to explore the creation and implementation of policy in three main areas: learning and teaching, Final Year Projects, and assessment. Finally, it reflects on student and staff perspectives on the policy, collected across two semesters, and considers how this information might be used for future enhancement of the policy process.